Rural Market Food Diversity and Farm Production Diversity: Do They Complement or Substitute Each Other in Contributing to a Farm Household's Dietary Diversity? - Nandi, Ravi; Nedumaran, Swamikannu (Frontiers in Sustainable Food Systems, 2022)
Majority of undernourished people live in rural Asia and Africa, and many of them are smallholder farmers and consume a significant amount of what they produce. This is specifically true in India. However, in the context of increasing commercial production systems, it is not well-known how much food is consumed from a particular food group that was purchased, what proportion of food is from the production of farm households, and how their diets change seasonally. Furthermore, whether the rural market food diversity complements or substitutes farm production diversity in household's diets is unknown. We employed a mixed-methods research design to answer these questions. The research was conducted in three villages in Telengana State. The results reveal that crop diversity has significantly declined from a highly-diverse production system to a less diverse one. The Food Consumption Score results show that on average own-farm production contributes 23% of food (mainly starchy staples), while market purchases contribute 77% of calories consumed (from more diverse and nutritious foods). Therefore, in the study, villages' market food diversity is more important, and it is complementary to own-farm production. However, our study shows that mere market access (the most widely used proxy indicator in the literature) does not guarantee the availability of diverse nutritious foods to households who use that specific market. This is because market food diversity varies from market to market and across seasons. Therefore, we proposed that in commercial production systems improving crop diversity, and strengthening rural markets, are needed. Moreover, incentivizing retail business and subsidizing nutritious and/or biofortified food in rural areas must be part of strategies to improve nutrition in rural India.